Sustainable consumption and hedonic event experiences: A conceptual framework and future research agenda - Francisco Tigre Moura; Cansu Hattula (IU Internationale Hochschule, 2024)
This paper proposes a novel conceptual framework to address the lack of sustainable consumption behaviors during live hedonic event experiences, such as music concerts or football games. The framework's rationale is founded on principles from the theory of planned behavior, theory of cognitive dissonance, affect heuristic theory and dual process model. It suggests an inversely directional flow of affective and cognitive responses throughout the stages of an event experience (experience anticipation, experience consumption and co-creation, and post-consumption). Further, it posits that the higher the consumers' affective response during a hedonic event experience (and consequent decline of cognitive evaluations), the lower is the likelihood to engage in sustainable consumption behaviors. Also, it includes multiple intrinsic, extrinsic, and situational factors that moderates the framework's rationale. Finally, the paper presents an agenda for future research to test and validate the theoretical rationale proposed in the framework.
Keywords: M31; 650; Sustainable consumption; hedonic experiences; leisure; live events; theory of planned behavior; theory of cognitive dissonance; affect heuristic theory